Physicochemical Properties and Antioxidant Potential of Tateishi Kazu Vegetable Soup - Kalsoom Kalsoom; Muhammad Hamayun; Muhammad Aaqil Khan; Yong-Sung Park; Il-Doo Kim; Dong-Hyun Shin; Amjad Iqbal (Journal of Food Quality)
Many industrialized areas of the world demand for the nutraceuticals due to rapidly growing health risks linked with higher consumption of processed foods. Tateishi Kazu vegetable soup or miracle soup is widely consumed around the world because of its nutraceutical properties. In the current research, the Tateishi Kazu vegetable soup was made from both organic and nonorganic sources, such as carrot, burdock root, shiitake mushroom, daikon radish, and radish leaves. We analyzed colour, antioxidant properties, cell viability, and mineral and free amino acid contents of both soups. The L∗a∗b and pH values revealed no drastic changes in the colour of the organic soup stored for 96 hours. The essential amino acids were present in higher amounts in an organic soup compared to the nonorganic soup. Similarly, the total mineral contents of the organic soup were higher than the nonorganic soup; however, potassium was the major mineral in both soups. Higher phenolic contents with elevated 2,2-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS), 2,2-diphenyl-1-picrylhydrazyl (DPPH), and superoxide dismutase (SOD) activity were noticed in organic soup. Moreover, both soups showed considerable reduction in cell viability of HepG2 cells tested through the MTT assay. From the present study, we concluded that the organic Tateishi Kazu vegetable soup can be of great importance to food industry due to the presence of viable nutrients and pharmacological properties.